2021
DOI: 10.5552/drvind.2021.1973
|View full text |Cite
|
Sign up to set email alerts
|

Examining Parameters of Surface Quality Performance of Paulownia Wood Materials Modified by Thermal Compression Technique

Abstract: The aim of this study was to evaluate the effect of thermal compression process on some surface properties of paulownia solid wood materials. The widest surface of wood samples was mechanically compressed at high temperatures. The duration was 45 min. Four different process combinations were created, including two temperatures (150 °C and 170 °C) and two pressure levels (20 bar and 22.5 bar). The surface roughness, wettability and color properties of treated and untreated samples were compared. The roughness p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Thus, the CW density change by the bleaching steps was not significant. The water contact angle (WCA) of the heat-treated CW increases the hydrophobic properties [24,25]. The authors indicated the effects of different heat treatments and compacted surfaces of CW.…”
Section: Swellingmentioning
confidence: 99%
“…Thus, the CW density change by the bleaching steps was not significant. The water contact angle (WCA) of the heat-treated CW increases the hydrophobic properties [24,25]. The authors indicated the effects of different heat treatments and compacted surfaces of CW.…”
Section: Swellingmentioning
confidence: 99%
“…The parameters used to characterise the wood surface properties are surface roughness and surface free energy (SFE) (Qin et al, 2014). Surface roughness is an important factor in determining surface quality, especially wettability (Akgul et al, 2012;Ayrilmis et al, 2009;Candan et al, 2010Candan et al, , 2012Candan et al, , 2021aCandan et al, , 2021bDarmawan et al, 2017;Dundar et al, 2008;Dundar et al, 2014;Unsal et al, 2010Unsal et al, , 2011Demir and Aydin, 2019). Parameters to determine the interaction between the wood surface and the coating material (wettability) can also be analysed by observing the thermodynamic wetting parameters, such as the SFE (Wålinder, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thermally modified wood is shown to have lower hygroscopicity, liquid water uptake, changed acidity, and anatomical structure (Jirouš-Rajković and Miklečić, 2019). It has also been shown that thermal modification has influence on the surface roughness and wettability of wood and wood-based materials (Candan et al, 2010;Unsal et al, 2011;Candan et al, 2012;Candan et al, 2021a). Thermal modification was shown to reduce the wettability and surface roughness of rowan (Sorbus aucuparia L.) wood (Candan et al, 2021b).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%